2014
DOI: 10.1002/pen.23876
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical model for the bulk polymerization of styrene chemically initiated by sequential and total decomposition of the trifunctional initiator diethyl ketone triperoxide

Abstract: This work experimentally and theoretically investigates the use of the symmetrical cyclic trifunctional initiator diethyl ketone triperoxide (DEKTP) in the bulk polymerization of styrene (St). The study focused on temperatures of 150 to 200 C, considering chemical initiation by both sequential and total decomposition reactions. The experimental work consisted of a series of isothermal batch polymerizations at higher temperatures, 150 and 200 C, with an initiator concentration of 0.01 mol/L. The mathematical mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…The experimental work consisted on the synthesis and characterization of the organic peroxide PDP and isothermal batch bulk polymerizations of St using the multifunctional initiators PDP and L331 at 0.01 mol/L. The experimental data for bulk polymerization of styrene using the trifunctional cyclic initiator DEKTP were taken from our previous work (Berkenwald et al 2013). The selected polymerization temperatures are such that initiator decomposition is mostly sequential (Cerna et al 2002; Casteñeda Facio 2007).…”
Section: Experimental Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental work consisted on the synthesis and characterization of the organic peroxide PDP and isothermal batch bulk polymerizations of St using the multifunctional initiators PDP and L331 at 0.01 mol/L. The experimental data for bulk polymerization of styrene using the trifunctional cyclic initiator DEKTP were taken from our previous work (Berkenwald et al 2013). The selected polymerization temperatures are such that initiator decomposition is mostly sequential (Cerna et al 2002; Casteñeda Facio 2007).…”
Section: Experimental Workmentioning
confidence: 99%
“…With respect to initiator structure, it was observed that the use of cyclic multifunctional initiators (e.g..: triperoxide cyclohexanone (CHTP), diethylketone triperoxide (DEKTP), acetone triperoxide (ATP), cyclohexanone diperoxide (CHDP) and pinacolone diperoxide (PDP)) in polymerization reactions represents a promising alternative (Sheng et al 2004;Castañeda Facio 2007;Berkenwald et al 2013;Berkenwald et al 2015). Sheng et al (2004) experimentally studied the use of the cyclic trifunctional initiator 3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxonane in the bulk polymerization of St.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The medium cis ‐PB was provided by Dynastol Elastómeros S.A de C.V., México ( trueM¯n=215 000 g/mol, trueM¯w=410 000 g/mol). Cyclic initiators DEKTP and PDP were synthesized and characterized as in our previous work .…”
Section: Methodsmentioning
confidence: 99%
“…Detailed FRIG kinetic modeling studies differentiating between all apparent termination chain length dependencies are scarce. As shown in Table 1, most studies are deterministic and focus on the modeling of average characteristics applying average-based termination models, specifically the wp -like models [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67]; some models are even intrinsic [68][69][70][71][72][73]. One of the most detailed deterministic models has been developed by Estenoz and Meira [68] considering isothermal solution FRIG of PB with St, able to acceptably match experimental data for monomer conversion, average molar mass, and grafting efficiency.…”
Section: Introductionmentioning
confidence: 99%